Masalah Matematika Autentik pada Pembelajaran IKRAR untuk Meningkatkan Kemampuan Berpikir Kritis - Ni Made Suastini; I Gusti Putu Sudiarta; I Made Ardana (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to develop AMP (Authentic Mathematical Problems) that are valid, practical, effective, and know the characteristics of AMP to improve critical thinking ability. This study uses a Research Based Design approach with discussion and analysis of problems, planning, repetitive cycles, and reflection. AMP were implemented using the IKRAR learning model (Initiation, Construction-Reconstruction, Application, and Reflection) with effective questions. The trial was conducted at SD N 1 Ubud involving fifth grade students and a teacher. The validity data was collected by conducting expert tests that were adjusted to the validity assessment instruments components of AMP. The practicality data was collected through questionnaires and observation sheets in learning activities then analyzed descriptively. The effectiveness data was collected through critical thinking ability tests consisting of AMP. The characteristics data of AMP was collected based on studies, physical form, and findings during the trials. The results show that the AMP in IKRAR learning to improve critical thinking ability are valid, practical, and effective. The characteristics of AMP are based on real life problems, can measure critical thinking ability, encourage students to be interested in determining solutions, train students to think divergently, and do not use presupposition words (for example: if, suppose, etc).